Well-being at work and working conditions of kindergarten and primary school teachers - Sigursteinsdóttir, Hjördís (Menntavísindasvið Háskóla Íslands, 2018)
Health is a key factor of well-being in all aspects of life, not least work-related life. Health, as defined by the World Health Organization (WHO), encompasses a state of complete physical, mental, and social well-being and not merely the absence of disease or infirmity (World Health Organization, 1986). Antonovsky (1988) argued that good health partly depends on whether individuals respond to a difficult situation in a positive or a negative way, and their ability to see the context of the conditions they face (Antonovsky, 1988). Our well-being in the workplace can have a major impact on our lives. Several scholars have defined a healthy workplace as one where employees feel safe and satisfied, that supports good health, well-being and the ability to cope, stimulates activity towards development of the workplace, hinders accidents, and reduces absenteeism and stress (Kauppinen et al., 2007; Whitehead, 2006).The aim of the study was to examine the well-being at work and working conditions of municipal employees, particularly kindergarten and primary school teachers. Four research questions were asked: (1) How did kindergarten and primary school teachers feel at the end of the work day for the past three months? (2) Did kindergarten and primary school teachers feel differently at the end of the work day for the past three months than other municipal employees? (3) What is the connection between working conditions of kindergarten and primary school teachers and a feeling of being stressed at the end of the workday? (4) What is the connection between working conditions of kindergarten and primary school teachers and a feeling of exhaustion at the end of the workday? This study is based on an electronic questionnaire survey submitted to all employees of one municipality in Iceland (total 1,566) in autumn 2016. The response rate was 70.2%. Kindergarten and primary school teachers were 45.2% of the respondents.The results show that 35.4% of kindergarten and primary school teachers were very often or rather often ...